Diffusion-controlled excitation annihilation in Sr2₂CeO₄ crystal - Masalov, A.A.; Viagin, O.G.; Ganina, I.I.; Malyukin, Yu.V. (Functional Materials, 2009)
The contribution from interaction between regular optical centers in Sr2₂CeO₄crystal structure to the migration process of electronic excitation energy has been demonstrated. The Sr2₂CeO₄ crystals have been synthesized by the Pechini citrate method. The luminescence decay process has been studied as a function of the laser radiation density. Parameters of excitation mobility have been estimated. It is shown that the migration in strontium- cerium oxide is rather weak; during its lifetime, the excitation migrates over the 4 chain sites in the arrangement of the optical centers. Продемонстровано внесок взаємодії регулярних оптичних центрів у кристалічній структурі Sr2₂CeO₄ до процесу міграції енергії електронного збудження. Зразки Sr2₂CeO₄ синтезовано цитратним методом Печіні. Досліджено криві загасання люмінесценції Sr2₂CeO₄ залежно від густини лазерного випромінювання. Визначено параметри рухливості збудження. Показано, що міграція у цераті стронцію відносно слабка, за час життя збудження долає 4 вузли ланцюжка у системі оптичних центрів. Показан вклад взаимодействия регулярных оптических центров в кристаллической структуре Sr2₂CeO₄ в процесс миграции энергии электронного возбуждения. Образцы Sr2₂CeO₄ синтезированы цитратным методом Печини. Исследованы кривые затухания люминесценции Sr2₂CeO₄ в зависимости от плотности лазерного излучения. Определены параметры подвижности возбуждения. Показано, что миграция в церате стронция относительно слабая, за время жизни возбуждение преодолевает 4 узла цепочки в системе оптических центров.